Neuroprotection - New Approaches and Prospects 2020
DOI: 10.5772/intechopen.91192
|View full text |Cite
|
Sign up to set email alerts
|

Glyproline Pro-Ampakine with Neuroprotective Activity

Abstract: Previously it was shown that neuropeptide cyclo-L-prolylglycine (CPG) is a positive modulator of AMPA receptors, which increases BDNF level in neuronal cell cultures. The spectrum of CPG's pharmacological effects corresponds to that of BDNF. Dipeptide N-phenylacetyl-glycyl-L-proline ethyl ester (GZK-111) was designed and synthesized as a linear analog of CPG. The aim of the present work was to reveal the pharmacological profile of GZK-111. Dipeptide GZK-111 was shown to metabolize into CPG in vitro and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The experiences from animal studies suggested strong relationships between AD-associated abnormalities and brain fatty acid metabolism. AD-related pathologies inhibited homeostatic and regenerative functions of neural stem cells via perturbation of fatty acid metabolism [ 57 ]. The ACADM gene is responsible for producing medium-chain acyl-CoA dehydrogenase (MCAD) enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The experiences from animal studies suggested strong relationships between AD-associated abnormalities and brain fatty acid metabolism. AD-related pathologies inhibited homeostatic and regenerative functions of neural stem cells via perturbation of fatty acid metabolism [ 57 ]. The ACADM gene is responsible for producing medium-chain acyl-CoA dehydrogenase (MCAD) enzyme.…”
Section: Resultsmentioning
confidence: 99%